DOP11 Lymphocyte activation gene (LAG)-3 on T cells is a potential therapeutic target in ulcerative colitis. (25th January 2019) - Slevin, S; Tan, M; Lahiff, C; Wang, L M; Greenaway, B; Lynch, K; Geremia, A; Hughes, S; Leavens, K; Nevin, K; Marks, D J B; Tarzi, R; et al.
Abstract: Background: LAG-3 is a transmembrane protein expressed on T cells following antigen-driven activation. Although it functions as a negative co-stimulatory receptor, similar to PD-1 and CTLA-4, its expression identifies lymphocytes that may contribute to initiation and persistence of inflammation in patients with inflammatory disease. We quantified LAG-3 expression in patients with ulcerative colitis before and after treatment, and characterised the sub-populations of activated T cells in the mucosa that express LAG-3, examining in particular effector cells, memory cells, and regulatory cells. Previously we presented an initial characterisation of LAG-3 + T cells; here we extend our findings with RT-PCR and functionally characterise lamina propria LAG-3 + T cells with intracellular cytokine staining. Methods: High-dimensional flow cytometric analysis on blood and inflamed and non-inflamed colonic biopsy samples from patients with ulcerative colitis ( n = 42) and non-IBD controls ( n = 9) was performed. Immunohistochemical analysis on mucosal samples was used to determine the correlation of LAG-3 + cells with endoscopic and histological scores, as well as the impact of biologic therapies. Cytokine production from mucosal LAG-3 + cells was determined by flow cytometry and quantitative RT-PCR. Results: The frequency of LAG-3 + cells in peripheral blood was negligible (<0.5%), regardless of disease activity in patients. However, in the lamina propria, the frequency of LAG-3 + T lymphocytes was markedly increased in active UC compared with uninflamed and non-IBD controls ( p < 0.0001 and p = 0.001, respectively) and correlated positively with endoscopic score (UCEIS, p = 0.004, r = 0.43). LAG-3 expression was enriched on effector memory and CD161 + T cells. LAG3 mRNA levels were also increased in active disease ( p = 0.003 and p = 0.008, respectively) and correlated with the histological Nancy score ( p < 0.001, r = 0.68). Mucosal LAG-3 + T cells demonstrated robust production of IFNγ ( p = 0.04) and IL-17A ( p = 0.01) when stimulated ex vivo compared with LAG-3 − cells, with lower amounts of IL-10 detected ( p < 0.06). In patients undergoing treatment for ulcerative colitis, the number of LAG-3 + cells decreased in patients who responded to therapy ( p < 0.0001, n = 11), but remained elevated in non-responders ( p = 0.058, n = 12). Conclusions: LAG-3 expression is not altered in circulating blood. However, mucosal expression is increased in inflammation and normalises after successful treatment. Although some reports suggest that LAG-3 + cells have mainly regulatory functions, in human IBD, LAG-3 + cells are mainly effector memory cells and predominantly produce IFNγ, IL-17A, and low levels of IL-10. Therefore, depleting LAG-3 + cells is a promising strategy for IBD that merits further clinical investigation.